1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

# 15(x-9)-2(x-12)+5(x+6)=0,solve the equation

Open in App
Solution

## Simplifying the equation we get 15(x + -9) + -2(x + -12) + 5(x + 6) = 0 Reorder the terms: 15(-9 + x) + -2(x + -12) + 5(x + 6) = 0 (-9 * 15 + x * 15) + -2(x + -12) + 5(x + 6) = 0 (-135 + 15x) + -2(x + -12) + 5(x + 6) = 0 Reorder the terms: -135 + 15x + -2(-12 + x) + 5(x + 6) = 0 -135 + 15x + (-12 * -2 + x * -2) + 5(x + 6) = 0 -135 + 15x + (24 + -2x) + 5(x + 6) = 0 Reorder the terms: -135 + 15x + 24 + -2x + 5(6 + x) = 0 -135 + 15x + 24 + -2x + (6 * 5 + x * 5) = 0 -135 + 15x + 24 + -2x + (30 + 5x) = 0 Reorder the terms: -135 + 24 + 30 + 15x + -2x + 5x = 0 Combine like terms: -135 + 24 = -111 -111 + 30 + 15x + -2x + 5x = 0 Combine like terms: -111 + 30 = -81 -81 + 15x + -2x + 5x = 0 Combine like terms: 15x + -2x = 13x -81 + 13x + 5x = 0 Combine like terms: 13x + 5x = 18x -81 + 18x = 0 Solving -81 + 18x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '81' to each side of the equation. -81 + 81 + 18x = 0 + 81 Combine like terms: -81 + 81 = 0 0 + 18x = 0 + 81 18x = 0 + 81 Combine like terms: 0 + 81 = 81 18x = 81 Divide each side by '18'. x = 4.5 Simplifying x = 4.5 So by simplifying we get solution for the equation as 4.5

Suggest Corrections
1
Join BYJU'S Learning Program
Related Videos